2022
DOI: 10.1155/2022/6949117
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Values of Earthworm Species Extract from Azad Kashmir as Anticoagulant, Antibacterial, and Antioxidant Agents

Abstract: Aims. Current research aimed to explore the therapeutic values of different earthworms as antibacterial, anticoagulant, and antioxidant agents. Methods. Ten different earthworms, i.e., Amynthas corticis, Amynthas gracilis, Pheretima posthuma, Eisenia fetida, Aporrectodea rosea, Allolobophora chlorotica, Aporrectodea trapezoides, Polypheretima elongata, Aporrectodea caliginosa, and Pheretima hawayana, were collected and screened for biological activities. Antibacterial effect analysis of earthworm species was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…At the end, it was observed that the results established a directly proportional relationship between PBP and PCF concentrations and the biofilm inhibition percentage. Similarly, Mustafa et al [ 44 ] used the earthworms’ extract to check its effect on biofilm inhibition, cell proliferation, and the synergistic effect. They found that the earthworm extract inhibited the biofilm synthesis compared to the control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the end, it was observed that the results established a directly proportional relationship between PBP and PCF concentrations and the biofilm inhibition percentage. Similarly, Mustafa et al [ 44 ] used the earthworms’ extract to check its effect on biofilm inhibition, cell proliferation, and the synergistic effect. They found that the earthworm extract inhibited the biofilm synthesis compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the extract of A. gracilis also reduced the biofilm synthesis for S. aureus and S. pyogenes , while the extract of P. posthuma inhibited the biofilm formation for E. coli and K. pneumoniae. Likewise, body extracts of E. fetida reduced the biofilm development for P. aeruginosa [ 44 ]. Biofilm formation is based on various factors and their correlations, such as adhesions, growth, extracellular-binding proteins in matrix, biofilm architecture, and cell to cell communication, which play a vital role in formation as well as maturation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it has been consumed in various ways; in previous years, earthworm was advised to be edible for anemia and malaria 13 . Recent research dedicated that Allolobophora calignosa, which is an earthworm species that belong to the phylum Annelida 14 , possesses many activities such as antioxidant 11 , anticoagulant, antibacterial and anticancer 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The earthworm has proven a competitive medicinal importance in treating various diseases due to its biological activities. The body cavity of earthworms comprises a coelomic fluid, which has anti-inflammatory capabilities (16). Extract of earthworm (Pheretima aspergillum) increases osteoblast activity and inhibits the generation of osteoclasts (17).…”
Section: Introductionmentioning
confidence: 99%